Effect of Different Doses of Vermicompost Mixed with NPK Fertilizer on Summer Radish (Raphanus sativus L.) - Ali, M S; Aslam, H B; Mohammad, N; Rahman, M E; Anny, S F T Z; Munna, M H; Hossen, K (SAARC Journal of Agriculture, 2025)
Radish (Raphanus sativus L.) is a root vegetable widely known all over the world for its nutritional value. Bangladesh grows radish to meet high demand, but overuse of chemical fertilizers harms health and the environment. Integrating organic methods with reduced chemical fertilizers offers a sustainable solution. Keeping this in mind, a field experiment was conducted at A-To-Z Agro Farm, Bagatiprara, Natore, Bangladesh, during July to September 2024 to examine the growth and yield-contributing parameters of radish as affected by different doses of vermicompost mixed with NPK fertilizer. Four treatments and three replications were included in the randomized complete block design of the experiment. The treatments were, T0 (0 NPK + 0 vermicompost), T1 (100% NPK + 3 t ha-1 vermicompost), T2 (100% NPK + 6 t ha-1 vermicompost) and T3 (100% NPK + 9 t ha-1 vermicompost). The highest plant height (38.70 cm), number of leaves (15.96), leaf length (30.76 cm), leaf diameter (7.75 cm), root length (20.02 cm), root diameter (3.49 cm), root weight (108.27 g), gross yield (30.32 t ha-1), marketable yield (30.28 t ha-1) and benefit cost ratio (BCR) (2.37) were observed from treatment T3 (100% NPK + 9 t ha-1 vermicompost), whereas the lowest data were obtained from treatment T0 (Control). According to the results, T3 treatment, i.e., 100% NPK + 9 t ha⁻¹ vermicompost, showed improved growth, yield and yield-contributing characteristics of radish. SAARC J. Agric., 23(1): 212-223 (2025)